Tantangan dan Strategi Implementasi Kebijakan Anti-Korupsi di Lembaga Pemerintahan - Wahid, St. Hadijah; Putra, Wandi Pratama; Arale, Friska Amelia (Legal Standing : Jurnal Ilmu Hukum, 2025)
Corruption within government institutions is a major obstacle to achieving sustainable growth and building a clean governance system. Anti-corruption policies are important, but the complexity of their implementation encompasses cultural factors, laws, and power dynamics. Government institutions face difficulties in implementation due to complex bureaucratic structures, internal resistance, and limited resources. The purpose of this research is to identify the challenges and implementation strategies of anti-corruption policies in government institutions. This research uses literature review and data analysis methods. The results indicate that improvement efforts require strategies such as strengthening internal capacity, increasing transparency, and fostering public participation. A strong legal foundation, adequate resource distribution, as well as outreach and public education programs are key to enhancing anti-corruption policies in government institutions. Implementation strategies involve standardizing law enforcement, capacity building, strengthening legal frameworks, resource distribution, awareness campaigns, and anti-corruption capacity enhancement programs. Encouraging public participation, especially through anti-corruption education in schools, and leveraging information technology to increase transparency, are essential foundations for building a clean and effective government.